The Engineering Innovation Center Bridging the Industry and The Academe. - Abis, Leopoldo V.
Commercialization of technologies through licensing and patenting has been practiced worldwide. University-based licensing offices that bring university research and development outputs to the industry have become a major source of income for continued support for R&D activities. Industries involved in the transfer of technologies have benefited well with their collaboration. The Engineering Innovation Center is the unanimous response of the University of the Philippines College of Engineering, the National Engineering Center, the University of the Philippines Alumni Engineers, and the U.P. Engineering Research and Development Foundation, Inc. in promoting commercially the R&D outputs of the U.P. College of Engineering and the National Engineering Center. This paper presents the goals and strategy of Innovation Center as well as its present involvement and future plans.